Atypical peri-Gondwanan granodiorite–tonalite magmatism from Southern Iberia. Origin of magmas and implications - Castro, A. (2022)
An ensemble of fifteen granodiorite/tonalite plutons and minor intrusions was generated during CambroOrdovician times (ca. 498–462 Ma) at the margin of Gondwana, which occupies a large portion of the Central Iberian Zone of the Iberian Massif (Spain and Portugal). This ensemble is known as the Beira-Extremadura batholith (BEB), which is mainly composed of tonalities and granodiorites (>90 vol%) and shows an atypical composition, with values of ASI (alumina saturation index) ≈ 1.2 on average, and marked calc-alkaline affinity in terms of major and trace elements. SHRIMP zircon U-Pb ages of 476 ± 7 Ma, 476 ± 6 Ma, and 474 ± 7 Ma for Montánchez, Santa Cruz de la Sierra and Valdemorales tonalites, respectively, coincide within uncertainty with the age of other Lower Ordovician BEB intrusions. Analysis of phase relations and comparisons with experimental results on cotectic liquid compositions, indicate that these atypical rocks represent calc-alkaline magmas that carried exogenous pelitic restites from depth. Assimilation of partially molten metasediments by invasion of calc-alkaline magmas is a plausible explanation. Model mixing of experimental calc-alkaline liquids and Ediacaran metasedimentary rocks yields that 20% (up to 40% in samples of the Santa Cruz Pluton) of assimilated metagreywackes and metapelites is required to account for geochemical atypical compositions departing from a main cotectic array of calc-alkaline systems. The processes of melting or melting plus assimilation are favored by addition of water-rich fluids. We propose a tectonic scenario of crustal extension and metasomatized mantle melting that supplied hydrous intermediate magmas to the crust triggering crustal melting and massive assimilation of metasediments